2019
DOI: 10.1002/jbmr.3741
|View full text |Cite
|
Sign up to set email alerts
|

ΔFosB Requires Galanin, but not Leptin, to Increase Bone Mass via the Hypothalamus, but both are needed to increase Energy expenditure

Abstract: Energy metabolism and bone homeostasis share several regulatory pathways. The AP1 transcription factor ΔFosB and leptin both regulate energy metabolism and bone, yet whether their pathways intersect is not known. Transgenic mice overexpressing ΔFosB under the control of the Enolase 2 (ENO2) promoter exhibit high bone mass, high energy expenditure, low fat mass, and low circulating leptin levels. Because leptin is a regulator of bone and ΔFosB acts on leptin‐responsive ventral hypothalamic (VHT) neurons to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The GAL regulation of glucose and energy homeostasis was studied in animal models, where GAL-KO mice were glucose intolerant; data suggests that GAL might also play an inhibitory role in insulin secretion on a neuronal level [ 185 ]. In mice, an increase in metabolism and energy usage is caused by the ΔFosB over-expression mediated by hypothalamic neurons, which need GAL as the inducer [ 186 , 187 ]. In the central nervous system, GAL is co-expressed with serotonin and norepinephrine, of which both are involved in depressive disorder [ 188 ].…”
Section: Neuropeptides In Anxiety and Depressionmentioning
confidence: 99%
“…The GAL regulation of glucose and energy homeostasis was studied in animal models, where GAL-KO mice were glucose intolerant; data suggests that GAL might also play an inhibitory role in insulin secretion on a neuronal level [ 185 ]. In mice, an increase in metabolism and energy usage is caused by the ΔFosB over-expression mediated by hypothalamic neurons, which need GAL as the inducer [ 186 , 187 ]. In the central nervous system, GAL is co-expressed with serotonin and norepinephrine, of which both are involved in depressive disorder [ 188 ].…”
Section: Neuropeptides In Anxiety and Depressionmentioning
confidence: 99%
“…In previous studies, elevated concentrations of GAL have been detected in the fracture callus of fractured bones (McDonald et al 2003) and demonstrated potential to facilitate bone formation associated with injury by inhibiting excess TNF-α and IL-1β production (McDonald et al 2007). GAL is also necessary for the leptin-independent bone mass–inducing effects of the transcription factor ΔFosB on bone homeostasis via hypothalamic neurons (Idelevich et al 2018; Idelevich et al 2019). Thus, GAL is a prototypical neurogenic effector molecule involved in skeletal homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the extent to which neuropeptide‐producing neurons share bone regulatory functions remains to be elucidated. Previously, we showed that activator protein (AP1) antagonists are also capable of exerting strong regulation of energy metabolism and bone mass . AP1 antagonists are a family of transcription factors forming heterodimers between Jun and Fos proteins, regulating gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mice in which ΔFosB or the artificial AP1 antagonist dominant‐negative JunD (DNJunD) are stereotactically targeted to the ventral hypothalamus (VHT) recapitulate the ENO2‐ΔFosB phenotype . Recently, using AP1 antagonism as a tool, we showed that AgRP‐expressing or POMC‐expressing neurons are capable of inducing high trabecular bone mass and high energy metabolism, a process which requires the presence in the VHT of the neuromediator galanin . Here, using the same genetic neuron targeting approach, we investigated whether AP1 antagonism in NPY‐expressing and CART‐expressing neurons also produces changes in energy homeostasis and bone mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation